The overlooked role of the home in mass shooting fatalities - Wilson H. Hammett; Pragya Bhuwania; Jody Heymann (Injury Epidemiology)
Abstract Background Prevention efforts for mass shooting fatalities often focus on public events, overlooking where most fatalities occur. This study analyzes a comprehensive database to better inform prevention strategies. Methods Using data from the Gun Violence Archive (GVA), we identified 252 mass shooting events (2014–2023) with four or more deaths, excluding the perpetrator, resulting in 1,464 fatalities. A media analysis determined location and links to domestic violence. Mortality burden by location, age, gender, and domestic violence was calculated, with tests of association performed. Results We found that half (50%) of mass shooting fatalities occurred in homes—five times more than in businesses/workplaces (10%). Among children (0–9), 89% of fatalities occurred in homes, compared to 62% among older children and teens (10–17) and 44% among adults (18+). Women were more likely to be killed in mass shootings at home (50%) than men (40%). Fatalities were disproportionately concentrated in homes across all age groups (p < 0.001). Domestic violence-related mass shootings accounted for 46% of all fatalities, with 70% of fatalities from domestic violence-related events occurring in homes. Conclusions Public discourse neglects home-based mass shootings, which disproportionately affect women and children. Targeted interventions, especially addressing domestic violence, are critical for reducing fatalities.